The Effect of Scaffolding on Assignment Quality and Procedural Learning Achievement - Hendrikus Midun; Oswaldus Bule; Widdy H.F Rorimpandey (LED Edizioni Universitarie, 2020)
Some problems experienced by millennial students when they learn by online include learning control, learning disorientation, and cognitive load. This study aims to examine the effect of scaffolding use on assignment quality and procedural cognitive learning achievement in the implementation of inverted or flipped (IF) classroom strategies. This study involved students of the pre-service study program of Indonesian Catholic University of Ruteng. The total research subjects were 78 students. They were divided into experimental and control groups. The experimental group is assisted by scaffolding, while the control group without scaffolding. The study design used a pretest-posttest experimental control group design and data collection using questionnaires and tests. Data analysis using multivariate analysis (MANOVA). The results showed that the use of scaffolding increased the effectiveness of implementing IF classroom strategies on student assignment quality and procedural learning achievement. The implications of the research for future study and learning practices can be explained.